Adult Women with Congenital Adrenal Hyperplasia (CAH) - Ichsan Arif; Bobby Indra Utama; Muhammad Rudi Setiawan (Andalas Obstetrics And Gynecology Journal, 2022)
Introduction : Congenital Adrenal Hyperplasia (CAH) is the most common cause of ambiguous genitalia. It is a genetic disorder that occurs due to failure or disruption of the formation of enzymes which play a role in the production of cortisol and aldosterone and can cause fusion of the labia, clitoromegaly, and a fusion of the vagina and distal urethra.Case Reports:A 32-year-old patient, unmarried, came to the urogynecology department complaining of thickening of the upper genitalia that resembles male genitalia. This problem has been known to the patient since she was 16 years old and was brought to the doctor at the age of 21 and diagnosed with congenital adrenal hyperplasia. The patient has had menstruation since she was 14 years old, but it is irregular. Since 8 years ago, the patient has been regularly taking hydrocortisone from an internal medicine specialist but has never been to the obstetrics and gynecology department for 8 years, now the patient comes to the urogynecology department because she wants to get married. When the patient was in school, she grew up like a normal woman and have good academic abilities. In the family history, there was no family history of congenital abnormalities. From physical examination, her height is 150 cm. She shows the habitus of external body like a woman. On genital examination found no formation of labia, clitoromegaly. Karyotype 46, XX. Ultrasonography found uterus and ovaries within normal limits.Conclusion:Counseling, both surgical and non-surgical treatment with a multidisciplinary approach, will give good results in patients with CAH. Rapid diagnosis and treatment will provide good management for patients with CAH. Surgery in the form of reducing the size of the clitoris (while maintaining the function of sensation), as well as expanding the vaginal opening can help in these patients to improve the patient's quality of life.Keywords: Congenital Adrenal Hyperplasia; clitoromegaly; unmarried